2010
DOI: 10.1111/j.1365-2842.2010.02118.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Bruxism - associations with perceived stress, motivation for control, dental anxiety and gagging*

Abstract: To examine possible associations between self-reported bruxism, stress, desirability of control, dental anxiety and gagging. Five questionnaires were distributed among a general adult population (402 respondents): the Perceived Stress Scale (PSS), Desirability of Control Scale (DC), Dental Anxiety Scale (DAS), Gagging Assessment Scale (GAS), and Bruxism Assessment Questionnaire. A high positive correlation between DAS and GAS (R = 0·604, P < 0·001) was found. PSS was negatively correlated with DC (R = -0·292, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
160
2
21

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(215 citation statements)
references
References 33 publications
15
160
2
21
Order By: Relevance
“…These results were lower than those measured in our study but showed that awake bruxism was more prevalent than sleep bruxism. However, unlike the present study, the previous authors used only self-reports (without clinical examination) based on the memories of individuals and excluded subjects who were not aware of their bruxism; polysomnography and electromyography are the required exams for the gold standard of a final diagnosis of bruxism, but using these tests for large sample sets is expensive 10,16 . Because of this limitation, these tests were not used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were lower than those measured in our study but showed that awake bruxism was more prevalent than sleep bruxism. However, unlike the present study, the previous authors used only self-reports (without clinical examination) based on the memories of individuals and excluded subjects who were not aware of their bruxism; polysomnography and electromyography are the required exams for the gold standard of a final diagnosis of bruxism, but using these tests for large sample sets is expensive 10,16 . Because of this limitation, these tests were not used.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review concluded that the prevalence of awake bruxism in the adult population was 20%, while that of sleep bruxism was 8% 10 . Another study determined the prevalence of adults with sleep bruxism to be 14% and those with awake bruxism to be 31% 16 . These results were lower than those measured in our study but showed that awake bruxism was more prevalent than sleep bruxism.…”
Section: Discussionmentioning
confidence: 99%
“…11 Awake bruxism is the habit of clenching the teeth during wakefulness, and probably has a different cause and pathophysiology from sleep bruxism. 12 Despite this conceptual difference, it has been observed that their concomitant presence is frequent and that sleep bruxism significantly increases the odds for awake bruxism and vice-versa. 7 On the other hand, activities named as parafunctional habits are those that exceed the individual's physiologic tolerance, leading to the breakdown of the masticatory system.…”
Section: Introductionmentioning
confidence: 99%
“…The Gagging Assessment Scale (GAS) asks the patient how they feel in four situations, ranging from personal dental care (brushing ones teeth) to undergoing dental treatment in the back of the mouth [10]. The GAS asks the patients to score how nauseated they would feel in each situation on a scale from 1 (no nausea whatsoever), to 5 (experiencing actual throat spasms and occasionally throwing up).…”
Section: Predictive Gagging Survey Gagging Severity Indexmentioning
confidence: 99%